2000
DOI: 10.1046/j.1365-2559.2000.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphous low‐grade adenocarcinoma and adenoid cystic carcinoma: distinct architectural composition revealed by collagen IV, laminin and their integrin ligands (α2β1 and α3β1)

Abstract: Collagen IV and laminin, and their integrin ligands, are useful in demonstrating that neoplastic ductal units of PLGA are composed of a single cell layer, being distinct from ACC which contains structures composed of two layers of neoplastic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 27 publications
3
34
0
2
Order By: Relevance
“…We have already shown that integrins influence CAC2 cell interactions with laminin. Inhibiting the function of ␣3␤1 integrin, a receptor expressed in adenoid cystic carcinoma in vivo, 3 decreased the attachment of CAC2 cells to laminin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have already shown that integrins influence CAC2 cell interactions with laminin. Inhibiting the function of ␣3␤1 integrin, a receptor expressed in adenoid cystic carcinoma in vivo, 3 decreased the attachment of CAC2 cells to laminin.…”
Section: Discussionmentioning
confidence: 99%
“…2 Growth patterns are solid, tubular, and pseudocystic, and perineural invasion is a common histological finding. [1][2][3] Electron microscopy shows both luminal and myoepithelial cells, and these cells are often separated by extracellular matrix (ECM), such as pools of basal lamina, collagen fibers, elastin, and glycosaminoglycans. 2 A conspicuous finding in the cribriform variant of adenoid cystic carcinoma is a thickened band of extensively duplicated basement membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, while many immunohistochemical stains (e.g., c-kit, Ki-67, glial fibrillary acidic protein, CD43, S100, bcl-2, etc.) have been used to aid in this differential diagnosis, none of them distinguishes these tumors in a consistently reliable manner [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…1 On the other hand, extracellular materials (ECMs) including type IV collagen, laminin heparan sulfate proteoglican, and entactin have been found in immunohistochemistory and in electron microscopy in AdCC. [2][3][4][5][6] In cytology, the ECM shows various shapes and to date there is no consensus opinion on the ECM shapes and AdCC patterns. [7][8][9] In this study, we examined both the imprint and fineneedle aspiration cytological smears of seven tumors histologically diagnosed as AdCC, focusing on morphological characteristic of the ECM.…”
mentioning
confidence: 99%